(untitled) (Research, Society and Development, 2021)
This study aims to obtain information on the most expressive intelligent mobility systems implemented in the main cities of the world, analyze the data and discuss their effects in favor of improving the population’s quality of life. This is a narrative literature review study, with a qualitative and exploratory approach. The material collection process was carried out from November 2020 to June 2021, using the Scielo, Scopus, Web of Science, ScienceDirect, Wiley and Proquest (ASIA) databases. The articles analyzed allow us to say that smart mobility is an integrated system composed of several projects and actions aimed at sustainability, governments and private institutions started to develop promising initiatives for the urban mobility segment, through ICT tools in order to solve the problems arising from the impacts of urbanization. In fact, the results of the installation of technological instruments to collect data in cities and the interconnectedness of information enable the creation of intelligent service delivery models with the potential to measure the quality of the thematic axis of mobility, as well as providing opportunities for well-being of citizens and the industrial development of the city.